On Modality of Auxiliary Verbs in Mongolian and Korean - Davaajav, Urtnasan (Altaica, 2025)
The present study examines the modal meanings of auxiliary verbs through a contrastive analysis of Mongolian and Korean. The study focuses on auxiliary verb constructions such as -aad4/-j,ch üzekh and -aad4/-j,ch ögökh in Mongolian, and -eo/a boda and -eo/a juda in Korean. These auxiliary verbs express not only aspectual meanings but also meanings that are not directly related to aspect. The modal meaning of auxiliary verbs is closely associated with the speaker’s stance and attitude toward the event, and it can be identified only through the structural relationship between the auxiliary verb and the main verb. In order to clarify the modal meanings of auxiliary verbs, examples from the two languages were analyzed contrastively. The results show that modal meanings can be categorized into subject-oriented and speaker-oriented types. For instance, constructions involving the auxiliary verb ‘see/try’ in both languages convey modal meanings such as “attempt” or “trying to do” a feature that is also observed in other languages such as Kyrgyz and Japanese, indicating a cross-linguistically common phenomenon. Auxiliary verbs function not only to express modal meanings related to the subject’s action such as attempt, effort, support, encouragement, and emphasis but also tend to become increasingly abstract, most often developing speaker-oriented modal meanings. Монгол, солонгос хэлний туслах үйл үгийн баймж утгa Хураангуй: Энэхүү өгүүлэлд туслах үйл үгийн баймж утгыг монгол, солонгос хэлний хүрээнд зэрэгцүүлэн авч үзнэ. Судалгаанд монгол хэлний -аад4/-ж,ч үзэх, -аад4/-ж,ч өгөх, солонгос хэлний -어/아 보다 (-eo/a boda), -어/아 주다 (-eo/a juda) зэрэг туслах үйл үгсийг хамруулав. Эдгээр туслах үйл үг нь байдлын утгыг илэрхийлэхээс гадна зарим тохиолдолд байдлын утгатай шууд холбоогүй, өөр төрлийн утга илрүүлдэг байна. Туслах үйл үгийн баймж утга нь өгүүлэгчийн тухайн үйл явдалд хандаж буй байр суурь, хандлагатай нягт холбоотой бөгөөд зөвхөн гол үйл үгтэй холбогдсон бүтцийн хүрээнд тодорхойлогддог. Иймээс туслах үйл үгийн баймж утгыг тодорхойлох зорилгоор дээрх хоёр хэлний жишээг зэрэгцүүлэн шинжилсний дүнд баймж утга нь өгүүлэгдэхүүн төвтэй болон өгүүлэгч төвтэй гэсэн хоёр төрөлд хуваагддаг болохыг онцлон авч үзэв. Тухайлбал, монгол, солонгос хэлний ‘үзэх’ туслах үйл үг оролцсон үгийн бүтцэд “оролдох, хийхийг завдах” гэсэн баймж утга илэрч байгаа нь киргиз, япон зэрэг бусад хэлэнд мөн ажиглагддаг бөгөөд энэ нь олон хэлний нийтлэг шинж болохыг харуулж байна. Туслах үйл үг нь өгүүлэгдэхүүний үйл хөдлөлийг илтгэх оролдох, зүтгэх, дэмжих, тэтгэх, онцлох зэрэг баймж утгыг илэрхийлэх үүрэгтэйгээс гадна ихэнх тохиолдолд илүү хийсвэржиж, өгүүлэгч төвтэй баймж утга илэрхийлэх хандлагатай байдаг. Түлхүүр үг: үйл үг, туслах үйл үг, үгийн сангийн утга, баймж, өгүүлэгч төвтэй баймж, өгүүлэгдэхүүн төвтэй баймж